Пропозиції щодо удосконалення нормативно-правових документів для забезпечення радіаційної безпеки під час перетворення об’єкта "Укриття" - Городецький, Д.В.; Деренговський, В.В.; Павловський, Л.І. (Проблеми безпеки атомних електростанцій і Чорнобиля, 2017)
Проаналізовано досвід по забезпеченню норм із радіаційної безпеки під час виконання робіт у радіаційно-небезпечних зонах об’єкта «Укриття». Показано, що виявлені проблеми потребують внесення відповідних доповнень до тексту діючих нормативно-правових актів, що регламентують радіаційну безпеку, або створення нових спеціальних нормативних документів для вирішення проблем радіаційної безпеки під час перетворення об’єкта «Укриття» на екологічно безпечну систему у складі комплексу НБК-ОУ. Проанализирован опыт по обеспечению норм радиационной безопасности при выполнении работ в радиационно-опасных зонах объекта «Укрытие». Показано, что выявленные проблемы требуют внесения соответствующих дополнений в текст действующих нормативно-правовых актов, регламентирующих радиационную безопасность, или создание новых специальных нормативных документов для решения проблем радиационной безопасности при преобразовании объекта «Укрытие» в экологически безопасную систему в составе комплекса НБК-ОУ. The application of regulatory and legal measures is the basis of the entire radiation safety system of any radiation-nuclear facility, which ensures that the personnel and the environment do not exceed and optimize doses of radiation. The need for correction (adaptation) of existing documents regulating normative-legal measures is revealed in the process of their practical application, especially in such complicated and unique radiation conditions, which characterizes the object "Ukryttya". The analysis of experience gained in previous years on the implementation of the Shelter Implementation Plan (SIP) on the object "Ukryttya" revealed a number of problems in ensuring an acceptable level of radiation safety during work in particularly dangerous areas, namely: the problem of setting individual control levels (CL) of an individual annual effective dose for the Contractor's personnel and the design control levels (DCL) for work in undeveloped or unoccupied premises; the complexity of choosing the optimal variant of design and technical solutions, which should be considered using the method "Cost-benefit analysis"; the question of the appropriateness of decontamination of materials, equipment and other building structures that are dismantled during the execution of works on the SIP; lack of requirements and procedures for the implementation of the ALARA Management Plan in the implementation of SIP projects. The solution of the above-mentioned problems is possible by making appropriate amendments (additions) to the text of the existing regulatory acts regulating radiation safety, or the creation of new, special regulatory documents, which takes into account the problems that arise during the work on the object "Ukryttya".